Sistema deposicionais e estudos de proveniência sedimentar do Supergrupo Espinhaço e do Grupo Macaúbas na porção ocidental do Anticlinal de Itacambira (MG) - Mariana Meireles Leite (2013)
This study proposes the use of facies analysis and studies of sedimentary provenience in the Espinhaço and Macaúbas (rift fase) proterozoic basins, in the region of Espinhaço Setentrional, north of MG state. The study area is located in the east side of Itacambira anticline, the most important morphological feature in area. The crescent number of geochronological data about the proterozoic sedimentary sequences in the area of Araçuaí Orogen creates the need of more solid material to correlated these units and achieve a better understand of the them. The approache used in this work is the facies analysis combined with the provenience stydies. The data collected is based on sedimentary profiles in 1:5000 and 1:25000 scale. Within these profiles a compilation map were made. In this mapping were recognized the Porteirinha Complex (gneiss and granitoids), the sadstones of Espinhaço Supergroup (Resplandecente and Matão formations) and the Macaúbas Group represented by Duas Barras and Serra do Catuní formations. The provenience studies were based in isotopic analysis (U-Pb in dentritical zircons), catodoluminescence of quartz, and geochemical data. For the Espinhaço Basin were recognized a sag fase with deposition in arid conditions of the Resplandecente desert, followed by the incursion of a shallowsea and deposition of Matão formation. The Matão Formation was deposited in a shoreline system dominated by Swach zone and longshore stream. Above this sequence in erosive discordance occurs the Duas Barras Formation related to an alluvial fan and a braided river system. This unit represents the rift sequence of Macaúbas Basin. The provenience studies revels that the Porteirinha Block represents the most important source of Espinhaço units, with ages between 3174±10Ma to 1805±140Ma. In Duas Barras Formation mesoproterozoic sources are more representative, although proterozoic and archean sources are still present. The maximum sedimentation age is 1198±31Ma.